Putting metaphysics first essays on metaphysics and epistemology - Devitt, Michael, 1938- (Oxford : Oxford University Press, 2010)
Michael Devitt presents a series of essays in which he argues for an uncompromisingly realist view of the external physical world. He goes on to reject moral noncognitivism & antirealist views of truth. He argues against the a priori, & urges that we should approach epistemology & semantics from a metaphysical perspective & not vice versa.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics; Knowledge, Theory of; Semantics (Philosophy)